Meteorology at the millennium - Pearce, R. P. (Robert Penrose), 1924- (International geophysics series, 2002)
Meteorology at the Millennium details recent advances in meteorology and explores its interfaces with science, technology, and society. Ways in which modern meteorology is contributing to the developments in other sciences are described, as well as how atmospheric scientists are learning from colleagues in related disciplines. Meteorology at the Millennium will serve as a point of reference for students and researchers of meteorology and climatology for many years to come. The areas covered include weather prediction at the millennium, climate variability and change, atmosphere-ocean coupling, the biogeochemical system, weather on other planets. This book is a compilation of the best invited papers presented at a conference celebrating the 150 years of the Royal Meteorological Society (RMS).